2002
DOI: 10.1002/dvdy.10128
|View full text |Cite
|
Sign up to set email alerts
|

Extensive vascularization of developing mouse ovaries revealed by caveolin‐1 expression

Abstract: Expression screening for genes preferentially expressed in mouse fetal ovaries relative to testes identified Cav-1 as a candidate female-specific gene. Cav-1 encodes caveolin-1, a component of the cell membrane invaginations known as caveolae, which are involved in lipid regulation and signal transduction. In situ hybridization revealed high levels of Cav-1 mRNA in developing ovaries, compared with moderate or low levels in testes. Analysis of caveolin-1 protein distribution by immunofluorescence showed this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…Vascular development of the XX gonad appears to be the result of proliferation and extension of the branches of the primordial gonadal vasculature (Fig. 1 A) (20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular development of the XX gonad appears to be the result of proliferation and extension of the branches of the primordial gonadal vasculature (Fig. 1 A) (20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…In both XX and XY gonads, the vasculature continued to develop from endothelial cells in the initial vascular branches that undergo proliferation during this period (20)(21)(22). Whether additional endothelial cells arise de novo within the XX or the XY gonad cannot be determined in these assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of Cav-1 in the vasculature has also been highlighted by Bullejos et al, who observed high levels of Cav-1 mRNA in the developing ovaries but not testes. 15 This difference is due to the formation of a more dense and more complex vascular network in the ovaries. 15 …”
mentioning
confidence: 99%
“…15 This difference is due to the formation of a more dense and more complex vascular network in the ovaries. 15 …”
mentioning
confidence: 99%